'They call 'im Crowie': an investigation of the Aboriginal significance attributed to a wrecked River Murray barge in South Australia. (1st March 2017) - Roberts, Amy; Duivenvoorde, Wendy; Morrison, Michael; Moffat, Ian; Burke, Heather; Kowlessar, Jarrad; Naumann, John; ,
Abstract : The Indigenous intangible heritage related to wrecked vessels has been poorly studied and documented. This article provides a counter to dominant maritime archaeology discourses via the investigation of the Aboriginal significance attributed to a wrecked and submerged River Murray barge ( Crowie ) in South Australia. There are numerous layers of Aboriginal significance that may be attributed to Crowie including the relationship of the community with their 'underwater country', Indigenous contributions to the riverboat industry, and the use of Aboriginal terms in vessel‐naming practices. Geophysical data from multibeam and sidescan sonar surveys allowed for confirmation of the proposed location of the wreck and through comparison with historical descriptions and photographs provided evidence to substantiate the assignation of the wreck as the Crowie barge. Abstract : 他们称其为 Crowie ༚南澳大利亚墨累河平底沉船被给予的土著含义研究 与土著无形遗产因素相关的沉船遗-一直以来鲜有研究或记载。本文通过对失事并沉没于南澳大利亚墨累河的平底沉船 ( Crowie 号) 被给予的土著含义展开调查, 反驳-主流海洋考古论述。 Crowie 号可能被赋予-不同层次的土著含义, 包括土著共同体与他们的"水下城"之间的关系、河船工业中的土著贡献以及在船舶命名方面使用土著词汇的习惯等。多光束及侧扫声纳等地球物理测量数据确认了推测的沉船地点, 在比较过史实描述及历史照片所提供的证据后可证实该沉船即为 Crowie 号驳船。 他們稱其為 Crowie ༚南澳大利亞墨累河平底沈船被給予的土著含義研究 與土著無形遺產因素相關的沉船-跡壹直以-鮮有研究或記載。本文通過對失事並沈沒於南澳大利亞墨累河的平底沉船 ( Crowie 號) 被給予的土著含義展開調查, 反駁-主流海洋考古論述。 Crowie 號可能被賦予-不同層次的土著含義, 包括土著共同體與-們的"水下城"之間的關系、河船工業中的土著貢獻以及在船舶命名方面使用土著詞匯的習慣等。多光束及側掃聲納等地球物理測量數據確認了推測的沉船地點, 在比較過史實描述及歷史照片所提供的證據後可證實該沉船即為 Crowie 號-船。